INTRODUCTION TO A SOCIAL-FUNCTIONAL APPROACH IN THE INDONESIAN CONSUMER PROTECTION LAW - Shidarta, Shidarta; Koos, Stefan (Faculty of Law, Parahyangan Catholic University, 2019)
This legal study, using a social-functional approach, underscores the importance of developing a viable social consumer protection system. Through it the government should promote a more effective consumer protection system in which any obstacle hampering consumer’s ability to obtain information necessary to make rational choices can be prevented. In short, a system protecting consumer’s right to obtain information. In this context, business enterprises are still expected to participate and support consumer protection movements at the national as well as regional level in which the end goal is to develop a fair business competition climate.